A novel mutation in the mitochondrial tRNASer(UCN) gene in a family with non-syndromic sensorineural hearing impairment. Issue 9 (1st September 2000) - Hutchin, Tim P; Parker, Mick J; Young, Ian D; Davis, Adrian C; Pulleyn, Louise J; Deeble, Jayne; Lench, Nicholas J; Markham, Alex F; Mueller, Robert F
Abstract : We describe a family with non-syndromic sensorineural hearing impairment inherited in a manner consistent with maternal transmission. Affected members were found to have a novel heteroplasmic mtDNA mutation, T7510C, in the tRNA Ser(UCN) gene. This mutation was not found in 661 controls, is well conserved between species, and disrupts base pairing in the acceptor stem of the tRNA, making it the probable cause of hearing impairment in this family. Sequencing of the other mitochondrial tRNA genes did not show any other pathogenic mutations. Four other mutations causing hearing impairment have been reported in the tRNA Ser(UCN) gene, two having been shown to affect tRNA Ser(UCN) levels. With increasing numbers of reports of mtDNA mutations causing hearing impairment, screening for such mutations should be considered in all cases unless mitochondrial inheritance can be excluded for certain.